A Retrospective Study of the Histopathological Spectrum of Erythema Nodosum Leprosum - Varniraj Patel; Rhea Ahuja; Sudheer K. Arava; Sujay Khandpur; Neetu Bhari; Vishal Gupta; M. Ramam (Wolters Kluwer Medknow Publications, 2024)
Background: There are no recent studies with a focus on the histopathology of erythema nodosum leprosum (ENL). Objectives: To describe the histopathological spectrum of ENL. Materials and Methods: Digital records from the pathology department were searched, and 125 slides were included. The histopathologic findings were recorded using a pre-designed proforma. Results: Several patterns were noted with the most common being a superficial and deep, perivascular and peri-appendageal, well-circumscribed dermal infiltrate that was seen in 70 (56.0%) biopsies. Other dermal patterns included a similar but loose infiltrate in 19 (15.2%) biopsies, diffuse dermal involvement in 9 (7.2%), top-heavy in 9 (7.2%), and bottom-heavy infiltrates in 12 (9.6%). Subcutaneous tissue was included in 107 biopsies. Extension of dermal infiltrates to the subcutis was noted in 71 (66.4%) biopsies and predominant involvement of the subcutis was noted in 6 (4.8%) biopsies, with lobular involvement in 60 (56.1%), septal involvement in 3 (2.8%), and septo-lobular involvement in 14 (13.1%). In 30 (28.0%) biopsies, the subcutaneous fat was uninvolved. The infiltrates contained neutrophils and foamy histiocytes in variable proportions, along with lymphocytes and plasma cells. Eosinophils were noted occasionally. Medium and/or small vessel vasculitis was noted in 11 (8.8%) biopsies. Fite-Faraco staining was available for 112 biopsies and revealed mainly fragmented and granular acid-fast bacilli (AFB) in 29 (25%) biopsies. Limitations: Our study had a retrospective design; we could not compare the lesional age and clinical characteristics of patients with the histological features. Conclusion: ENL is characterized by dermal infiltrates composed of foamy histiocytes and neutrophils in varying proportions arrayed in different dermal patterns. Extension of dermal infiltrates into the subcutis was frequent but absent in some. Predominant or exclusive involvement of the subcutis was rare. Vasculitis was noted in a small minority, while AFB were demonstrated in about a quarter of cases.